HIGH-RESOLUTION SPECTROMETRIC ANALYSIS OF RARE EARTH ELEMENTS-ACTIVATED CATHODOLUMINESCENCE IN FELDSPAR MINERALS - Gotze J.; Habermann D.; Neuser R.D.; Richter D.K. (My University, 1999)
Cathodoluminescence (CL) investigations of igneous, metamorphic and sedimentary feldspars indicate that rare earth elements (REE)-activated CL in feldspars is more common than previously assumed. Hot-cathode CL microscopy combined with high-resolution spectrometric analysis of CL emission allow to detect some REE below the detection limits of electron microprobe and proton-induced X-ray emission analysis (PIXE) and reveal variations in the REE distribution within single feldspar crystals. Differently luminescing zones can reflect changes during feldspar crystallization and/or element fluctuations during secondary alteration processes which are not discernible using conventional polarizing microscopy. The results of the study document Eu2+, Sm3+, Dy3+, Tb3+, and Nd3+-activated CL in feldspars of different origin. The influence of the crystal field on shape and position of REE luminescence spectra significantly differs for divalent and trivalent REE ions. Whereas Eu2+ shows a broad band emission (~420 nm) which is influenced by the local crystal field, trivalent ions of the rare earth show narrow emission lines which reflect the transitions between excited state wave functions lying inside closed electronic shells. The positions of these peaks and the characteristic energies are described for the different REE3+.
Keywords: HOT-CATHODE CL MICROSCOPY; HIGH-RESOLUTION SPECTROMETRIC ANALYSIS; RARE EARTH ELEMENTS; CATHODOLUMINESCENCE; FELDSPAR